2019
DOI: 10.1542/peds.2018-3301
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Nonmedical Immunization Exemptions in California and School-Entry Vaccine Status

Abstract: BACKGROUND AND OBJECTIVES: California implemented Senate Bill 277 (SB277) in 2016, becoming the first state in nearly 30 years to eliminate nonmedical exemptions from immunization requirements for schoolchildren. Our objectives were to determine (1) the impacts of SB277 on the percentage of kindergarteners entering school not up-to-date on vaccinations and (2) if geographic patterns of vaccine refusal persisted after the implementation of the new law. METHODS: At the state level, we analyzed the magnitude and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 19 publications
0
77
2
1
Order By: Relevance
“…In 2015, California became the third US state to eliminate all non-medical exemptions, and the first state to do so in more than three decades. This change in the law was preceded by a 2014 administrative initiative to reduce the misuse of a school admission process involving 'conditional entrants' -children who have started the required vaccination schedule but haven't completed it 6 . (Since 1979, children in California have been allowed to attend school as conditional entrants -but before 2014, only some schools followed up with parents, and some children were never fully vaccinated 6 .…”
Section: Exemptions and Penaltiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, California became the third US state to eliminate all non-medical exemptions, and the first state to do so in more than three decades. This change in the law was preceded by a 2014 administrative initiative to reduce the misuse of a school admission process involving 'conditional entrants' -children who have started the required vaccination schedule but haven't completed it 6 . (Since 1979, children in California have been allowed to attend school as conditional entrants -but before 2014, only some schools followed up with parents, and some children were never fully vaccinated 6 .…”
Section: Exemptions and Penaltiesmentioning
confidence: 99%
“…However, this change seems to be mainly associated with the administrative crackdown on conditional entrants. Following the elimination of non-medical exemptions, many parents with strong objections to vaccination simply acquired medical exemptions instead, educated their children at home, enrolled them in independent study programmes that do not require classroom-based instruction, or found other loopholes 6 .…”
Section: Exemptions and Penaltiesmentioning
confidence: 99%
“…In 2016, California eliminated all nonmedical exemptions. 1 Delamater et al 21 studied the rate of medical exemptions in California before and after the legislative change, finding that medical exemptions decreased in the first year after the change. However, by the second year, medical exemption rates rose, and geographic analyses showed that the areas with rising medical exemption rates coincided with areas that previously had high rates of nonmedical exemptions.…”
Section: Figurementioning
confidence: 99%
“…The case of California highlights the importance of studying exemption trends across time. We see that there is a plunge in exemptions following the removal of non-medical exemptions followed by an increase in the exemption level, perhaps indicating that vaccine hesitant individuals found other means to obtain exemptions 3,4,18 . Figure 4 demonstrates total exemptions across data reported years by state, broken down into medical exemptions, religious exemptions, philosophical exemptions, or unknown.…”
Section: Technical Validationmentioning
confidence: 88%